النظام القانوني لمزودي خدمات التصديق الإلكتروني في القانون الجزائري - بلحارث, ليندة (جامعة الوادي University of Eloued, 2018)
ملخص: نظرا لتطور التجارة الإلكترونية وما يتبعها من تطور تقنيات الدفع الإلكتروني، استدعى الأمر ضرورة إعادة النظر في عملية التوقيع الإلكتروني الذي أصبح ذو تقنيات عالية وعديدة مع ضرورة الاعتراف به قانونا وتنظيمه تنظيما دقيقا للتأكيد على قيمته الثبوتية، مع وضع مبدأ التكافؤ الوظيفي بينه وبين التوقيع الكلاسيكي. كما كان لابدّ من إيجاد ضمانات كفيلة لإرساء الأمان القانوني في مثل هذا التوقيع من طرف جهات تكون محايدة وموضع ثقة، سُمّيت بعدّة تسميات، كجهة التصديق الإلكتروني أو مورد خدمات التصديق أو مؤدي خدمات التصديق الإلكتروني ... إلخ، حيث تسهر هذه الأخيرة على ضمان الدخول القانوني لمنظومة التشفير باعتبارها منظومة سرية جدّا وحكرا على الدولة، بهدف ضمان تأمين سرية الخدمات الإلكترونية. لذلك أولى المشرع الجزائري أهمية بالغة لمثل هذه الجهات، من خلال تعريفه لنا لها، ووضع نظام قانوني خاص بها لاسيما القانون رقم 15/04، من خلال تبيان مختلف الشروط القانونية الواجب توافرها لممارسة نشاط مؤدي خدمات التصديق الإلكتروني وكذا الآثار القانونية المترتبة عن عملية التصديق الإلكتروني. Abstract: Due to the development of e-commerce and the development of e-payment technologies, it was necessary to review the process of electronic signature, which has become a high and diverse technology, which needs to be recognized by law and well organized to confirm its identification value, with the establishment of the principle of functional equivalence between it and the classic Signature. It was also necessary to find guarantees to establish the legal security in such a signature by parties that are neutral and trustworthy, named by several labels such as the electronic certification authority or the supplier of certification services or the providers of electronic certification services … etc, to ensure legal access to the system of change as a very confidential system and the rule of the state, in order to ensure the secrecy of electronic services. Thus, the Algerian legislator attaches great importance to such bodies, through its definition to us and the development of its own legal system, especially Law No. 15/04, by specifying the legal conditions that are required for the activity of the performer of the electronic certification services as well as the legal implications of the electronic certification process.
Keywords: المعاملات الإلكترونية، التوقيع الإلكتروني، التصديق الالكتروني، مزود خدمات التصديق، شهادة التصديق، المسؤولية